Persistence of exhaustion in cured hep C - Kaplan, David E. (Blood, 2017)
In this issue of Blood, Del Padre et al(1) evaluated the impact of eliminating chronic antigen exposure on B-cell exhaustion in the human therapeutic setting of direct-acting antiviral therapy for chronic hepatitis C virus infection (HCV) complicated by mixed cryoglobulinemia (MC). The phenotype of hepatitis C–related MC B cells has been previously demonstrated by this group and others(2) to include low-level CD21 expression (CD21(low)) and hypoproliferation in response to stimulation either through the B-cell receptor or Toll-like receptor 9, imperfectly termed “exhausted” or “anergic.” At baseline, CD21(low) B cells from HCV-infected patients expressed markers of chronic activation, with elevated and near-maximal basal levels of phosphorylated extracellular signal–regulated kinase, and were also predisposed to apoptosis. During oral direct-acting antiviral therapy, the authors observed that by 4 weeks (at which point, most patients have no circulating HCV RNA), these basal abnormalities at least partially normalized. During longitudinal follow-up after patients were documented as cured, the overall frequency of CD21(low) cells progressively declined from 50% to 30% of circulating B cells. However, the frequency of V(H)1-69(+) B cells specific for HCV-related MC generally remained stable, although some regained CD21 expression. Despite partial resolution of the exhaustion phenotype, surviving V(H)1-69(+) B cells remained hypoproliferative upon Toll-like receptor 9 ligation, suggesting that the B-cell exhaustion phenotype is durably programmed into antigen-specific B cells during long-term extracellular antigen exposure.